Analysis and Planning of Citraland Cirebon Residential Area Development - Erick Wahyu Frisdiantoro; Awliya Tribhuwana (Indonesian Journal of Advanced Research, 2026)
The development of residential areas requires comprehensive planning to ensure land suitability, adequate infrastructure, and compliance with spatial planning regulations. CitraLand Cirebon is one of the integrated residential developments in Cirebon City that continues to expand in response to increasing housing demand. This study aims to analyze the existing condition of the residential area and formulate appropriate development planning based on land suitability, infrastructure, public facilities, utilities, and spatial planning conformity. The research employed a descriptive qualitative approach using a case study method. Primary data were collected through field observations and documentation, while secondary data were obtained from planning documents, spatial planning regulations, and supporting information provided by the developer. The collected data were analyzed descriptively by comparing the existing conditions with the planned development and applicable spatial planning policies. The results indicate that CitraLand Cirebon has developed progressively with adequate accessibility, internal road networks, drainage systems, and supporting public facilities. Nevertheless, several parts of the area still require further infrastructure improvement and spatial arrangement to optimize residential functions and support sustainable development. The study concludes that land suitability, the availability of infrastructure, public facilities and utilities (PSU), and compliance with spatial planning regulations are the primary factors influencing the successful development of the residential area. Therefore, further development should prioritize infrastructure enhancement, integrated spatial planning, and sustainable environmental management to improve residential quality and ensure long-term urban development.